Nanometer composite dielectric thin film with laminated structure and preparation method of nanometer composite dielectric thin film

Through the design of nanocomposite dielectric film with laminated structure, the P(VDF-HFP) material filled with Ni(OH)2@PDI nanosheets and Ni(OH)2 nanosheets is used to regulate the number and thickness of layers to distribute electric fields and hinder electron transmission, solving the problem of improving energy storage density and efficiency of dielectric capacitors, and achieving synchronous improvement of high breakdown field strength and high energy storage density.

CN119517621AActive Publication Date: 2025-02-25NINGBO UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411429383.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-25
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

Existing dielectric capacitors have difficulties in improving energy storage density and efficiency, especially under the low filling content of inorganic ceramics, the dielectric constant cannot be significantly increased, but when the filling content increases, the breakdown field strength drops sharply.

Method used

A nanocomposite dielectric film with a stacked structure is formed by alternately stacking the pressure-bearing layer and the polarization layer. The pressure-bearing layer is polyvinylidene fluoride-hexafluoropropylene copolymer P(VDF-HFP) filled with Ni(OH)2@PDI nanosheets, and the polarization layer is P(VDF-HFP) filled with Ni(OH)2 nanosheets. The electric field is distributed and electron transport is hindered by regulating the number of layers and the thickness of each layer.

Benefits of technology

The synchronous improvement of breakdown field strength and dielectric constant was achieved, which significantly improved the energy storage density and efficiency, which was specifically manifested as a energy storage density of 32.1J/cm3 and an energy storage efficiency of 80.8% were obtained under a high breakdown field strength of 705.7MV/m.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517621A_ABST
    Figure CN119517621A_ABST
Patent Text Reader

Abstract

The invention discloses a nano composite dielectric film with a laminated structure and a preparation method thereof, and is characterized in that pressure-bearing layers and polarization layers are alternately laminated up and down to form 2-8 layers of nano composite dielectric films with the total thickness of 10-14 microns, and the preparation method comprises the following steps: coating the surface of a Ni (OH) 2 nanosheet with an organic matter PDI to obtain a Ni (OH) 2 (at) PDI nanosheet with a core-shell structure; the preparation method comprises the following steps: carrying out electrostatic spinning on a pressure-bearing layer solution in which the volume ratio of P (VDF-HFP) and Ni (OH) 2 (at) PDI nanosheets is 50% and a polarization layer solution in which the volume ratio of P (VDF-HFP) and Ni (OH) 2 (at) PDI nanosheets is 50%, and controlling the thickness ratio of the pressure-bearing layer to the polarization layer to be (6-3): (2-5) to obtain a primary nano-composite dielectric film, and finally carrying out hot-pressing film formation to obtain the nano-composite dielectric film with a laminated structure. The invention has the advantages that the breakdown field strength and the dielectric constant are synchronously improved, and the energy storage density is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dielectric capacitors, and in particular to a nano-composite dielectric film with a laminated structure and a preparation method thereof. Background Art

[0002] As human demand for energy storage continues to grow, dielectric capacitors have been widely used in electronic circuits, microwave communications, and power systems due to their high power density and ultra-fast charging and discharging speeds, and play an important role. However, the energy storage density and charging and discharging efficiency of dielectric capacitors are relatively low, which leads to an increase in their volume and weight, and part of the energy is lost in the form of heat. This is inconsistent with the trend of future energy storage devices to pursue efficient and stable storage and release of energy. Therefore, improving the energy storage density and efficiency of dielectric capacitors has become a focus of continuous attention for researchers. From the definition of the energy storage density of dielectric capacitors, it can be seen that the dielectric constant ε r and the breakdown field strength E b The square of the energy storage density U d It is directly proportional to the breakdown field strength, so it is more effective to increase the energy storage density by increasing the breakdown field strength. Among the materials used as dielectrics, organic polymers tend to have higher breakdown field strengths, while inorganic ceramics have higher dielectric constants. At present, the method of increasing energy storage density by increasing the breakdown field strength is to compound inorganic ceramics with organic polymers to combine the high breakdown field strength of organic polymers and the high dielectric constant of inorganic ceramics.

[0003] In the initial design, researchers found that inorganic ceramics can be divided into zero-dimensional (0D), one-dimensional (1D) and two-dimensional (2D) fillers according to their shapes. Many studies have shown that 2D fillers have a larger aspect ratio than the other two and can serve as electron scattering centers to extend the electrical tree path. However, composite films still have problems such as electric field distortion and poor compatibility at the interface. Researchers generally use materials with similar dielectric constants and core-shell structures to solve these problems. In addition, researchers also use organic shells to increase the compatibility between fillers and substrates to reduce the defects caused by the addition of fillers. However, there is a difficult balance challenge in the performance of composite films. At low filling content of inorganic ceramics, although the breakdown field strength of the film is high, the dielectric constant cannot be significantly improved; when the filling content of inorganic ceramics increases, the dielectric constant increases, but the breakdown field strength drops sharply. This mutually restrictive phenomenon makes it extremely difficult to further improve the energy storage density of composite films, which brings new bottlenecks to the development and application of composite dielectric materials. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a nano-composite dielectric film with a laminated structure and a preparation method thereof, which can achieve synchronous improvement of breakdown field strength and dielectric constant and improve energy storage density.

[0005] The technical solution adopted by the present invention to solve the above technical problems is: a nano-composite dielectric film with a laminated structure, which is composed of a pressure-bearing layer and a polarization layer alternately stacked up and down to form 2 to 8 layers of nano-composite dielectric film with a total thickness of 10 to 14 microns, wherein the pressure-bearing layer is polyvinylidene fluoride-hexafluoropropylene copolymer P(VDF-HFP) filled with Ni(OH)2@PDI nanosheets, and the polarization layer is P(VDF-HFP) filled with Ni(OH)2 nanosheets.

[0006] Preferably, the volume percentage of the Ni(OH)2@PDI nanosheets added to P(VDF-HFP) is 1.3%, and the volume percentage of the Ni(OH)2 added to P(VDF-HFP) is 2%. The density of the prepared material is measured by the water displacement method, and then the volume of the added material is calculated and converted into the corresponding volume fraction content. The volume fraction can intuitively express the spatial proportion of the doping material in the composite medium.

[0007] Preferably, the pressure-bearing layer and the polarization layer are alternately stacked up and down to form 4 layers of nanocomposite dielectric film with a total thickness of 10 to 14 microns, and the thickness ratio of the pressure-bearing layer to the polarization layer is (6 to 3): (2 to 5).

[0008] Preferably, the pressure-bearing layer and the polarization layer are alternately stacked up and down to form 4 layers of nano-composite dielectric film with a total thickness of 12 microns, and the thickness ratio of the pressure-bearing layer to the polarization layer is 5:3.

[0009] The present invention also provides a method for preparing the above-mentioned nanocomposite dielectric film with a laminated structure, comprising the following steps:

[0010] Step 1: Prepare Ni(OH)2 nanosheets by hydrothermal method:

[0011] Step 2: coating the surface of Ni(OH)2 nanosheets with organic perylene-3,4,8,10-tetracarboxylic dianhydride (PDI) to obtain Ni(OH)2@PDI nanosheets with a core-shell structure;

[0012] Step 3: Electrostatic filament film formation:

[0013] (1) dissolving Ni(OH)2@PDI nanosheets in N,N-dimethylformamide (DMF), dispersing by ultrasonication, and then stirring by magnetic force until the mixture is uniformly mixed to obtain a Ni(OH)2@PDI nanosheet solution with a volume fraction of 1.3%;

[0014] (2) dissolving Ni(OH)2 nanosheets in N,N-dimethylformamide (DMF), dispersing by ultrasonication, and then stirring by magnetic force until the mixture is uniformly mixed, to obtain a Ni(OH)2 nanosheet solution with a volume fraction of 2.0%;

[0015] (3) P(VDF-HFP) was added to the Ni(OH)2@PDI nanosheet solution, and stirred at 60°C for 2 h at a magnetic force of 600 r / min, and then stirred at room temperature for 4 h to obtain a pressure-bearing layer solution with a volume ratio of P(VDF-HFP) to Ni(OH)2@PDI nanosheet of 50%;

[0016] (4) adding P(VDF-HFP) to the Ni(OH)2 nanosheet solution, stirring at 600 r / min magnetic force and 60°C for 2 h, and then stirring at room temperature for 4 h to obtain a polarization layer solution with a volume ratio of P(VDF-HFP) to Ni(OH)2 nanosheets of 50%;

[0017] (5) subjecting the pressure-bearing layer solution and the polarization layer solution to vacuum treatment to remove bubbles, respectively, and forming a composite film structure according to any one of claims 1 to 4 by alternating the pressure-bearing layer and the polarization layer up and down to electrospinning at a rate of 1 mm / min in an environment of a temperature of 40° C. and a humidity of 30° C., and controlling the thickness ratio of the pressure-bearing layer to the polarization layer to be (6-3):(2-5) by the spinning time, collecting the mixture on aluminum foil, and then placing the mixture in an oven at 60° C. for 2 h to remove residual solvent, thereby obtaining a preliminary nanocomposite dielectric film;

[0018] Step 4: hot-press the preliminary nanocomposite dielectric thin film prepared in step 3 to obtain a nanocomposite dielectric thin film with a laminated structure.

[0019] Further, step 1 is as follows: 6.5 g NiCl2 and 4 g NaOH are dissolved in 25 ml deionized water respectively, and magnetically stirred at 600 r / min for 30 minutes until completely dissolved, and then the NiCl2 solution is slowly dripped into the NaOH solution and 80 ml deionized water is added to mix, and then magnetically stirred at 600 r / min for 30 minutes, poured into a high-pressure reactor, and fully reacted at 200°C for 24 hours. The reaction product is centrifuged and washed several times with deionized water, and then vacuum dried at 60°C for 24 hours, and then ground to obtain light green Ni(OH)2 nanosheets.

[0020] Further, step 2 is as follows: 0.3 g Ni(OH)2 nanosheets and 0.02 g PDI are added to 30 ml deionized water in sequence, stirred at 60°C for 12 hours, and dried at 60°C for 12 hours to obtain Ni(OH)2@PDI nanosheets with a core-shell structure.

[0021] Furthermore, step 4 is as follows: the preliminary nano-composite dielectric film prepared in step 3 is pasted on the conductive surface of the conductive glass, and is hot-pressed in a vacuum vulcanizer at 150°C and a pressure of 15Mpa for 30 minutes. After the hot pressing is completed, the composite dielectric film is placed in an oven at 200°C for 10 minutes, and then quickly placed in an ice-water mixture to complete the quenching operation. After cleaning and drying, a nano-composite dielectric film with a laminated structure is obtained.

[0022] Compared with the prior art, the advantages of the present invention are: a nano-composite dielectric film with a laminated structure and a preparation method thereof can reasonably distribute the electric field by regulating the number of layers and the thickness of each layer of the multilayer structure, and hinder electron transmission at the interface, so that the electric tree grows horizontally along the interface, which helps to improve the insulation capacity of the multilayer film. In addition, NPP can capture electrons multiple times in the 4-layer structure, hinder carrier transmission, and enhance the breakdown field strength. Keeping the total thickness unchanged, regulating the thickness of the NP layer allows the NP to provide a sufficiently high polarization while allowing the NPP to bear as much electric field as possible within the tolerable range, which helps to further enhance the breakdown field strength. The 37.5vol.% NP / NPP composite film was optimized and prepared. Its appropriate number of layers and thickness allow it to maintain a high breakdown field strength and dielectric constant, and ultimately achieve the highest energy storage performance, and obtain an excellent 32.1J / cm at a high breakdown field strength of 705.7MV / m. 3 The energy storage density and energy storage efficiency are 80.8%.

[0023] In summary, the nanocomposite dielectric film with a laminated structure and the preparation method thereof of the present invention can significantly improve the overall energy storage performance of the composite material by regulating the number of layers and the thickness of each layer, so that the composite material has excellent breakdown resistance and dielectric properties. In addition, the preparation process is green and environmentally friendly, the process is simple, and it can be widely used. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the structure of four layers of nanocomposite dielectric film with different thicknesses;

[0025] Figure 2 This is a scanning electron microscope microscopic morphology of the nanocomposite dielectric film:

[0026] Figure 3 PE curves of different numbers of layers of nanocomposite dielectric films;

[0027] Figure 4 Energy storage density and efficiency diagram of different number of layers of nanocomposite dielectric films;

[0028] Figure 5 This is a simulation diagram of electrical breakdown of nanocomposite dielectric films with different numbers of layers;

[0029] Figure 6 PE curves of nanocomposite dielectric films with different thicknesses;

[0030] Figure 7 The energy storage density and efficiency diagram of nanocomposite dielectric films with different thicknesses;

[0031] Figure 8 This is a simulation diagram of electrical breakdown of nanocomposite dielectric films of different thicknesses. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below with reference to the accompanying drawings.

[0033] Polyvinylidene fluoride-hexafluoropropylene copolymer P(VDF-HFP) and polymethyl methacrylate PMMA were purchased from Shanghai Sanaifu New Materials Co., Ltd. DMF N,N-dimethylformamide (AR, 99.5%), NaOH sodium hydroxide (AR, 99.5%), nickel chloride NiCl2·6H2O (AR, 99.5%), and perylene-3,4,8,10-tetracarboxylic dianhydride (PDI) were purchased from Aladdin. 1. Specific embodiments

[0035] Example 1

[0036] A nanocomposite dielectric film with a laminated structure, which is formed by alternating pressure-bearing layers and polarization layers to form a 4-layer nanocomposite dielectric film with a total thickness of 12 microns, wherein the pressure-bearing layer is P(VDF-HFP) filled with Ni(OH)2@PDI nanosheets, and the polarization layer is P(VDF-HFP) filled with Ni(OH)2 nanosheets. The specific steps of the preparation method are as follows:

[0037] Step 1. Prepare Ni(OH)2 nanosheets by hydrothermal method: dissolve 6.5g NiCl2 and 4g NaOH in 25ml deionized water respectively, stir magnetically at 600r / min for 30 minutes until completely dissolved, then slowly drip the NiCl2 solution into the NaOH solution and add 80ml deionized water to mix, stir magnetically at 600r / min for 30min, pour into a high-pressure reactor, react at 200°C for 24h, wash the reaction product with deionized water for several times by centrifugation, and then dry in vacuum at 60°C for 24h, and grind to obtain light green Ni(OH)2 nanosheets.

[0038] Step 2: Coat the surface of Ni(OH)2 nanosheets with organic perylene-3,4,8,10-tetracarboxylic dianhydride (PDI), as follows: add 0.3g Ni(OH)2 nanosheets and 0.02g PDI into 30ml deionized water in sequence, stir at 60°C for 12 hours, and dry at 60°C for 12 hours to obtain Ni(OH)2@PDI nanosheets with core-shell structure, abbreviated as N@P.

[0039] Step 3: Electrostatic filament film formation:

[0040] (1) 0.247 g Ni(OH)2@PDI nanosheets were dissolved in 11 mL N,N-dimethylformamide (DMF), and then magnetically stirred at 600 r / min for 30 min until the mixture was uniformly mixed to obtain a Ni(OH)2@PDI nanosheet solution with a volume fraction of 1.3%;

[0041] (2) 0.247 g of Ni(OH)2 nanosheets were dissolved in 11 mL of N,N-dimethylformamide (DMF), and then magnetically stirred at 600 r / min for 30 min until the mixture was uniformly mixed to obtain a Ni(OH)2 nanosheet solution with a volume fraction of 2.0%;

[0042] (3) 0.8 g P(VDF-HFP) was added to the Ni(OH)2@PDI nanosheet solution, and the mixture was stirred at 600 r / min magnetic force and 60°C for 2 h, and then stirred at room temperature for 4 h to obtain a pressure-bearing layer solution with a volume ratio of P(VDF-HFP) to Ni(OH)2@PDI nanosheets of 50%, and the pressure-bearing layer was abbreviated as NPP;

[0043] (4) adding 0.8 g of P(VDF-HFP) to the Ni(OH)2 nanosheet solution, stirring at 600 r / min magnetic force and 60°C for 2 h, and then stirring at room temperature for 4 h, to obtain a polarization layer solution with a volume ratio of P(VDF-HFP) to Ni(OH)2 nanosheets of 50%, the polarization layer being abbreviated as NP;

[0044] (5) The pressure-bearing layer solution and the polarization layer solution were vacuum treated to remove bubbles, and the pressure-bearing layer and the polarization layer were alternately stacked to form a 4-layer film with a total thickness of 12 μm. The film was electrospun at a rate of 1 mm / min in an environment of temperature 40°C and humidity 30. The thickness ratio of the polarization layer NP to the pressure-bearing layer NPP was controlled to be 3:5 by the spinning time. The film was collected on aluminum foil and then placed in an oven at 60°C for 2 h to remove the residual solvent, thereby obtaining a preliminary nanocomposite dielectric film.

[0045] Step 4, hot pressing film formation: The preliminary nano-composite dielectric film prepared in step 3 is pasted on the conductive surface of the conductive glass, and is hot pressed in a vacuum vulcanizer at 150°C and a pressure of 15 MPa for 30 minutes. After the hot pressing is completed, the composite dielectric film is placed in an oven at 200°C for 10 minutes, and then quickly placed in an ice-water mixture to complete the quenching operation. After cleaning and drying, a laminated nano-composite dielectric film (referred to as 37.5% NP / NPP composite dielectric film) is obtained.

[0046] Example 2

[0047] The same as the above-mentioned Example 1, except that in step 3 (5), the thickness ratio of NP to NPP is controlled to be 2:6 by spinning time, collected on aluminum foil, and then placed in an oven at 60°C for 2 hours to remove residual solvent, thereby obtaining 4 layers of 25% NP / NPP composite dielectric film.

[0048] Example 3

[0049] The same as the above-mentioned Example 1, except that: in step 3 (5), the thickness ratio of NP to NPP is controlled to be 4:4 (i.e., 50% NP / NPP composite dielectric film) by the spinning time, collected on aluminum foil, and then placed in an oven at 60°C for 2 hours to remove the residual solvent, thereby obtaining 4 layers of 50% NP / NPP composite dielectric film.

[0050] Example 4

[0051] The same as the above-mentioned Example 1, except that in step 3 (5), the thickness ratio of NP to NPP is controlled to be 5:3 by spinning time, collected on aluminum foil, and then placed in an oven at 60° C. for 2 h to remove residual solvent, to obtain 4 layers of 62.5% NP / NPP composite dielectric film.

[0052] Example 5

[0053] The difference is the same as the above-mentioned embodiment 1, except that the composite dielectric film is designed to be a two-layer nanocomposite dielectric film with a total thickness of 12 microns formed by alternately stacking a pressure-bearing layer NPP and a polarization layer NP, and the thickness of NP and NPP is controlled to be the same by the spinning time.

[0054] Example 6

[0055] The difference is the same as the above-mentioned embodiment 1, except that the composite dielectric film is designed to be composed of 8 layers of nano-composite dielectric film with a total thickness of 12 microns, formed by alternately stacking pressure-bearing layers NPP and polarization layers NP, and the thickness of NP and NPP is controlled to be the same by spinning time.

[0056] Control group

[0057] 0.3 g Ni(OH)2 nanosheets and 0.02 g PDI were added to 30 ml deionized water in sequence, stirred at 60 °C for 12 h, and then dried at 60 °C for 12 h to obtain core-shell structured Ni(OH)2@PDI nanosheets, abbreviated as N@P.

[0058] 0.247 g Ni(OH)2@PDI nanosheets were dissolved in 11 mL N,N-dimethylformamide (DMF), and then magnetically stirred at 600 r / min for 30 min until the mixture was uniformly mixed to obtain a Ni(OH)2@PDI nanosheet solution with a volume fraction of 1.3%;

[0059] 0.8 g P(VDF-HFP) was added to the Ni(OH)2@PDI nanosheet solution, stirred at 600 r / min magnetic force and 60°C for 2 h, and then stirred at room temperature for 4 h to obtain a pressure-bearing layer solution with a volume ratio of P(VDF-HFP) to Ni(OH)2@PDI nanosheets of 50%.

[0060] The pressure-bearing layer solution was vacuum treated to remove bubbles, and electrospun at a rate of 1 mm / min in an environment of temperature 40°C and humidity 30, and the thickness was controlled to 12 microns by spinning time. The film was collected on aluminum foil and then placed in an oven at 60°C for 2 hours to remove residual solvent. The film was then pasted on the conductive surface of the conductive glass and hot-pressed in a vacuum vulcanizer at 150°C and a pressure of 15 MPa for 30 minutes. After the hot pressing, the composite dielectric film was placed in an oven at 200°C for 10 minutes, and then quickly placed in an ice-water mixture to complete the quenching operation. After cleaning and drying, a single-layer nanocomposite dielectric film was obtained, which was recorded as 1.3 vol.% N@P / PVH (abbreviated as NPP). 1.3 vol.% N@P / PVH (NPP) obtained 21.7 J / cm at 569.0 MV / m 3 energy storage density.

[0061] 2. Experimental Results Analysis

[0062] Figure 1 Figure 1 is a schematic diagram of the structure of four layers of nanocomposite dielectric films with different thicknesses. Figure 1 As shown, the volume fraction ratio of NP to NPP layers in the four-layer composite dielectric films (reflected in thickness) is 2:6, 3:5, 4:4, and 5:3, corresponding to 25 vol.% NP / NPP, 37.5 vol.% NP / NPP, 50 vol.% NP / NPP, and 62.5 vol.% NP / NPP composite dielectric films.

[0063] Figure 2 The scanning electron microscope microscopic morphology of the nanocomposite dielectric film. Figure 2As shown, the cross-sectional morphology of the composite film prepared in Example 1 has no obvious defects, no obvious differences between layers, and the filler in the film is evenly distributed vertically to the electric field. This proves that the preparation method of the nanocomposite dielectric film of the present invention can reduce the holes and defects of the composite film and greatly improve the quality of the film. The preparation method basically realizes mechanized operation, which can reduce the impact of human operation errors on the finished film and facilitate actual production application.

[0064] Figure 3 The PE curves of different layers of nanocomposite dielectric films are shown in Figure 2. Figure 3 As shown, the 2, 4, and 8-layer composite films prepared in Examples 5, 3, and 6 have greater E b , and the dielectric constant corresponding to the slope is also improved. The 50 vol.% NP / NPP composite film prepared in Example 3 has a larger E compared with the 2-layer composite film prepared in Example 5 and the 8-layer composite film prepared in Example 6. b , which also helps to obtain higher energy storage performance at the same slope.

[0065] Figure 4 The energy storage density and efficiency diagram of different layers of nanocomposite dielectric films. Figure 4 As shown in the figure, the 2, 4, and 8-layer composite films prepared in Examples 5, 3, and 6 have a higher energy storage density (21.7 J / cm 3 ) has a preliminary improvement. The 50 vol.% NP / NPP composite film prepared in Example 3 has an E of 652.8 MV / m b Compared with the composite films of Examples 5 and 6, a higher 27.8 J / cm 3 The energy storage density shows that 4 layers of composite film are the layers with the best energy storage performance.

[0066] Figure 5 The electrical breakdown simulation diagram of nanocomposite dielectric films with different numbers of layers. Figure 5As shown, the electrical tree of the first layer of NPP is thicker, and at the interface between NPP and NP, the electrical tree grows obviously horizontally, and the path increases. This is because NPP can capture electrons and reduce the kinetic energy of electrons, which helps to hinder electron injection and transmission. Under the same NP content and applied electric field, the 50vol.% NP / NPP prepared in Example 3 did not break down, and the electrical tree just grew to the 4th layer of NP. This is because the third layer of NPP reduces the kinetic energy of electrons again on the basis of the first layer, and causes the electrical tree to branch, increasing the path. Under the action of the NPP layer and the interface, the electrical tree is eventually exhausted in the NP layer and no conductive path is formed. Interestingly, the 8-layer 50vol.% NP / NPP prepared in Example 6 does not have better insulation performance because of its more NPP layers. This is mainly because the NPP layer is too thin and the electrical tree has passed through before it effectively hinders carrier transmission. It can be seen that the effect of the NPP layer and the interface is significantly smaller than that of the 2-layer and 4-layer composite films, and the electrical tree grows downward faster and forms a conductive path. The simulation results well illustrate the effect of the number of layers on the breakdown field strength of 50 vol.% NP / NPP and are consistent with the experimental results.

[0067] Figure 6 The PE curves of nanocomposite dielectric films with different thicknesses are shown in Figure 2. Figure 6 As shown in the figure, as the volume percentage x% increases, the slope of the PE curve gradually increases, and at the same time, the breakdown field strength decreases with the increase of x, but the breakdown field strength of the 37.5vol.% NP / NPP composite film prepared in Example 1 does not decrease too much. This means that the 37.5vol.% NP / NPP composite film can achieve the best energy storage performance in the design of the 4-layer structure composite film.

[0068] Figure 7 The energy storage density and efficiency diagram of nanocomposite dielectric films of different thicknesses are shown in Figure 2. By calculating the PE curves of x vol.% NP / NPP under different electric fields, the energy storage density and energy storage efficiency of x vol.% NP / NPP are obtained, as shown in Figure 2. Figure 7 As shown. With the increase of electric field strength, the energy storage density gradually increases, while the energy storage efficiency first decreases and then increases. This is because as the electric field strength increases, the dipole orientation gradually moves toward the direction of the electric field. Since the 37.5 vol.% NP / NPP composite film prepared in Example 1 has a suitable thickness of each layer, it has a large dielectric constant while maintaining a high breakdown field strength. Finally, the 37.5 vol.% NP / NPP composite film achieved a maximum of 32.1 J / cm at a high breakdown field strength of 705.7 MV / m. 3 The energy storage density and energy storage efficiency are 80.8%.

[0069] Figure 8The figure is a simulation diagram of the electrical breakdown of nanocomposite dielectric films of different thicknesses. As the volume percentage x% increases, the closer the electrical tree is to the lower plate, the more conductive paths are generated. This is because the proportion of NP with poor insulation performance is increasing, and the NPP layer is beginning to be unable to withstand the gradually increasing electric field. Figure 8 As shown in the figure, electrons are accelerated by the thicker NP layer, and too little NPP can no longer effectively hinder electron transmission, and the electric tree directly penetrates the entire composite film from top to bottom. The 25 vol.% NP / NPP and 37.5 vol.% NP / NPP composite films prepared in Example 2 and Example 1 show similar insulation properties, and are better than the 50 vol.% NP / NPP and 62.5 vol.% NP / NPP composite films prepared in Example 3 and Example 4. The simulation results are consistent with the experimental results.

[0070] In summary, the present invention will have a high breakdown field strength E b NPP with high dielectric constant was placed on the upper layer as the pressure-bearing layer, and 2.0 vol.% Ni(OH)2 / PVH(NP) with high dielectric constant was placed on the lower layer as the polarization layer. In this order, 2-layer, 4-layer and 8-layer composite films NP / NPP were constructed, and the volume fractions of the two were the same. By comparison, it was found that the 4-layer 50 vol.% NP / NPP obtained a breakdown field strength of 652.8 MV / m when the polarization was not much different, which was higher than the 2-layer 50 vol.% NP / NPP and 8-layer 50 vol.% NP / NPP. Then, four 4-layer x vol.% NP / NPP composite films were obtained by adjusting the thickness of NP. 37.5 vol.% NP / NPP has the most suitable ratio. Each layer can be allocated to a suitable electric field and bring higher polarization, while not making the electron kinetic energy too large to cause the NPP layer to be unblocked. The 4-layer 37.5 vol.% NP / NPP composite film obtained an excellent 32.1 J / cm at the highest breakdown field strength of 705.7 MV / m. 3 The energy storage density is 2.5W and the high energy storage efficiency is 80.8%.

[0071] The above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by a person skilled in the art within the spirit and scope of the present invention shall also fall within the protection scope of the present invention.

Claims

1. A nanocomposite dielectric film with a laminated structure, characterized in that: A nanocomposite dielectric film with a total thickness of 10 to 14 microns is formed by alternately stacking a pressure-bearing layer and a polarization layer, wherein the pressure-bearing layer is P(VDF-HFP) filled with Ni(OH)2@PDI nanosheets, and the polarization layer is P(VDF-HFP) filled with Ni(OH)2 nanosheets.

2. The nanocomposite dielectric film of the laminated structure according to claim 1, characterized in that: The added volume percentage of the Ni(OH)2@PDI nanosheets in P(VDF-HFP) is 1.3%, and the added volume percentage of the Ni(OH)2 in P(VDF-HFP) is 2%.

3. The nanocomposite dielectric film of the laminated structure according to claim 2, characterized in that: The pressure-bearing layer and the polarization layer are alternately stacked up and down to form 4 layers of nano-composite dielectric films with a total thickness of 10 to 14 microns. The thickness ratio of the pressure-bearing layer to the polarization layer is (6 to 3): (2 to 5).

4. The nanocomposite dielectric film of the laminated structure according to claim 3, characterized in that: The pressure-bearing layer and the polarization layer are alternately stacked up and down to form 4 layers of nano-composite dielectric films with a total thickness of 12 microns. The thickness ratio of the pressure-bearing layer to the polarization layer is 5:

3.

5. A method for preparing a laminated nanocomposite dielectric film according to any one of claims 1 to 4, characterized in that The following steps are involved: Step 1: Prepare Ni(OH)2 nanosheets by hydrothermal method: Step 2, coating the surface of Ni(OH)2 nanosheets with organic perylene-3,4,8,10-tetracarboxylic dianhydride PDI to obtain Ni(OH)2@PDI nanosheets with core-shell structure; Step 3: Electrostatic filament film formation: (1) dissolving Ni(OH)2@PDI nanosheets in N,N-dimethylformamide, dispersing by ultrasonication, and then stirring by magnetic force until the mixture is uniform, to obtain a Ni(OH)2@PDI nanosheet solution with a volume fraction of 1.3%; (2) dissolving Ni(OH)2 nanosheets in N,N-dimethylformamide, dispersing by ultrasonication, and then stirring by magnetic force until the mixture is uniformly mixed, to obtain a Ni(OH)2 nanosheet solution with a volume fraction of 2.0%; (3) P(VDF-HFP) was added to the Ni(OH)2@PDI nanosheet solution, and stirred at 60°C for 2 h at a magnetic force of 600 r / min, and then stirred at room temperature for 4 h to obtain a pressure-bearing layer solution with a volume ratio of P(VDF-HFP) to Ni(OH)2@PDI nanosheet of 50%; (4) adding P(VDF-HFP) to the Ni(OH)2 nanosheet solution, stirring at 600 r / min magnetic force and 60°C for 2 h, and then stirring at room temperature for 4 h to obtain a polarization layer solution with a volume ratio of P(VDF-HFP) to Ni(OH)2 nanosheets of 50%; (5) subjecting the pressure-bearing layer solution and the polarization layer solution to vacuum treatment to remove bubbles, respectively, and forming a composite film structure according to any one of claims 1 to 4 by alternating the pressure-bearing layer and the polarization layer up and down to electrospinning at a rate of 1 mm / min in an environment of a temperature of 40° C. and a humidity of 30° C., and controlling the thickness ratio of the pressure-bearing layer to the polarization layer to be (6-3):(2-5) by the spinning time, collecting the mixture on aluminum foil, and then placing the mixture in an oven at 60° C. for 2 h to remove residual solvent, thereby obtaining a preliminary nanocomposite dielectric film; Step 4: hot-press the preliminary nanocomposite dielectric thin film prepared in step 3 to obtain a nanocomposite dielectric thin film with a laminated structure.

6. The method for preparing a laminated nanocomposite dielectric film according to claim 5, characterized in that Step 1 is as follows: 6.5 g NiCl2 and 4 g NaOH are dissolved in 25 ml deionized water respectively, and magnetically stirred at 600 r / min for 30 minutes until completely dissolved. Then, the NiCl2 solution is slowly dripped into the NaOH solution and 80 ml deionized water is added to mix. After magnetic stirring at 600 r / min for 30 minutes, the mixture is poured into a high-pressure reactor and fully reacted at 200°C for 24 hours. The reaction product is centrifuged and washed several times with deionized water, and then vacuum dried at 60°C for 24 hours, and then ground to obtain light green Ni(OH)2 nanosheets.

7. The method for preparing a laminated nanocomposite dielectric film according to claim 5, characterized in that Step 2 is as follows: 0.3 g Ni(OH)2 nanosheets and 0.02 g PDI are added to 30 ml deionized water in sequence, stirred at 60°C for 12 hours, and dried at 60°C for 12 hours to obtain Ni(OH)2@PDI nanosheets with a core-shell structure.

8. The method for preparing a laminated nanocomposite dielectric film according to claim 5, characterized in that Step 4 is as follows: the preliminary nano-composite dielectric film prepared in step 3 is pasted on the conductive surface of the conductive glass, and is hot-pressed in a vacuum vulcanizer at 150°C and a pressure of 15Mpa for 30 minutes. After the hot pressing is completed, the composite dielectric film is placed in an oven at 200°C for 10 minutes, and then quickly placed in an ice-water mixture to complete the quenching operation. After cleaning and drying, a nano-composite dielectric film with a laminated structure is obtained.

Citation Information

Patent Citations

  • Ferroelectric polymer-based dielectric thin film having laminated structure, preparation method and application thereof

    CN108587007A

  • TiO2 nano material doped double-layer polyvinylidene fluoride composite medium and preparation method thereof

    CN113045845A

  • Flaky core-shell structure-doped polyvinylidene fluoride copolymer composite film and preparation method thereof

    CN113527826A

  • Preparation method of hole transport layer and perovskite photovoltaic module

    CN115347123A

  • A substrate with a polar elastomer dielectric and a method of coating a substrate with a polar elastomer dielectric

    US20200115584A1